Tingkat Kesegaran Jasmani Peserta Didik SMA Negeri 1 Tondano - Andreas Apsalom Punu; Nolfie Piri; Yuliana Sattu (STIKES Columbia Asia Medan, 2025)
Physical fitness in the school environment requires special attention because it will support optimal teaching and learning outcomes. Physical fitness or good physical ability for students serves to maximize the ability of learning comfort. From the results of observations at SMA Negeri 1 Tondano school, PJOK practicum learning activities experienced a few obstacles due to the lack of willingness of students in carrying out PJOK practical learning activities, even though high school age children must be active in carrying out physical activity activities. However, there are still some students who do not participate in PJOK learning practice activities. This is because students do not know the importance of maintaining physical fitness through PJOK learning activities at school. The research method used in this research is a descriptive quantitative approach with a percentage using a survey method with test and measurement data collection techniques. The population in this study were students of SMA Negeri 1 Tondano as many as 557 students and a sample of 56 students. From the results of the 2.4 KM running test using descriptive statistical data calculation of a sample of 56 people taken from SMA Negeri 1 Tondano students and combined with frequency distribution tables, averages, and percentages, the results obtained state that the level of physical fitness of SMA Negeri 1 Tondano students is in the very poor category.